Students' attitudes towards digital culture: a field study on a sample of students of the Faculty of Arts and Humanities in Sfax - Monia Ben ayed (Social Empowerment Journal, 2023)
The study aimed to identify students' attitudes towards digital culture. The study adopted the descriptive approach using the questionnaire form and the open interview to collect data. The study was applied to a sample of 150 male and female students belonging to the Department of Sociology at the Faculty of Arts and Humanities in Sfax, and the study concluded that there are positive attitudes of students towards digital culture and their awareness of the importance of using modern technologies in the educational process, in addition to cultural dependence occupying the first place among the most negative of digital culture from their point of view, and the data revealed that the majority of students prefer traditional education to e-learning.